2021
DOI: 10.1038/s41598-021-98636-y
|View full text |Cite
|
Sign up to set email alerts
|

Anodal tDCS augments and preserves working memory beyond time-on-task deficits

Abstract: Transcranial direct current stimulation (tDCS) of the left dorsolateral prefrontal cortex (DLPFC) has been shown to promote working memory (WM), however, its efficacy against time-on-task-related performance decline and associated cognitive fatigue remains uncertain. This study examined the impact of anodal tDCS of the left DLPFC on performance during a fatiguing visuospatial WM test. We adopted a repeated measures design, where 32 healthy adults (16 female), underwent anodal, control and sham tDCS on separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…In healthy participants, anodal tDCS over the left DLPFC reduced vigilance deficits caused by sleep deprivation and improved subjective state fatigue scores ( 107 109 ). Furthermore, anodal tDCS sustained or even improved the working memory performance in an hour-long two-back task ( 110 ). Recently, we showed that a single dose of anodal tDCS successfully counteracted fatigability development in healthy participants and, in turn, reduced the increase in occipital alpha power and the decline in sensory gating resulting from fatigability ( 66 ).…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 99%
“…In healthy participants, anodal tDCS over the left DLPFC reduced vigilance deficits caused by sleep deprivation and improved subjective state fatigue scores ( 107 109 ). Furthermore, anodal tDCS sustained or even improved the working memory performance in an hour-long two-back task ( 110 ). Recently, we showed that a single dose of anodal tDCS successfully counteracted fatigability development in healthy participants and, in turn, reduced the increase in occipital alpha power and the decline in sensory gating resulting from fatigability ( 66 ).…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 99%
“…The study showed small improvements in hit rates and reductions in error rates for the tDCS compared with the sham control condition. In another study, Karthikeyan et al. (2021) examined effects of tDCS over the DLPFC in a fatiguing visuospatial n -back task.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen out of the 23 single-session tDCS experiments included in this review were published in the last 5 years, i.e., 2017–2021. Only 2 of them showed effects of tDCS on WM ( Karthikeyan et al. 2021 ; Schmicker et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological measures: The raw ECG signal taken at 128 Hz was preprocessed to remove any motion artifacts and the peak detection algorithm was used, R-peaks from the signal were collected (Karthikeyan et al, 2021). The root mean square of successive differences (RMSSD) and low-to-high frequency ratio (LF/HF) were the two HRV features extracted to detect variations in cognitive load.…”
Section: Measurementsmentioning
confidence: 99%